IMPLEMENTATION OF THE PRINCIPLES OF GOOD CORPORATE GOVERNANCE IN AN EFFORT TO IMPROVE THE PERFORMANCE OF PT PLN (PERSERO) - Yanti, Eli Delvi (Universitas Negeri Medan, 2022)
This research aims to find out how the implementation of the principles of Good Corporate Governance in an effort to improve the performance of PT PLN (Persero). This research uses qualitative descriptive analysis by collecting field data (field research), interviews with various informants, and collecting documents and data related to research needs. The results showed that PT PLN (Persero) ULP Sunggal had applied the principles of Good Corporate Governance in carrying out the company's activities. This can be seen from transparency by providing access and service information to facilitate customers through the PLN Mobile application. Accountability, has been carried out well, it is seen from employees who are quick in dealing with problems experienced by customers, such as problems with power failures, loss of meters, electrical problems due to natural disasters and others. Accountability, in providing accountability has been carried out, can be seen from PLN's commitment in responding to every complaint/suggestion addressed to PLN quickly and well. Independence, having a commitment to realize a PLN that is clean from Corruption, Collusion and Nepotism (KKN), one of which is realized through not accepting interventions in the form of bribes, gratuities and so on in every decision making carried out by PLN. Fairness, the real form of implementation of this principle can be seen from, PLN checks the e-KTP if the customer is registered with the Population Office as one of the underprivileged communities, the electricity usage tariff gets a waiver of payment of 50% of the normal tariff. The implementation of Good Corporate Governance can create value for the community (public), suppliers, distributors, governments, and investors, so that it will have a direct impact on the survival of the company.